Flexible Solar Cells: Mechanically Recoverable and Highly Efficient Perovskite Solar Cells: Investigation of Intrinsic Flexibility of Organic–Inorganic Perovskite (Adv. Energy Mater. 22/2015). Issue 22 (November 2015) - Park, Minwoo; Kim, Hae Jin; Jeong, Inyoung; Lee, Jinwoo; Lee, Hyungsuk; Son, Hae Jung; Kim, Dae‐Eun; Ko, Min Jae
Abstract : In article number 1501406, Dae‐Eun Kim, Min Jae Ko, and co‐workers report highly efficient and ITO‐free ultra‐flexible perovskite solar cells on a shape recovery polymer substrate. The solar cell shows not only outstanding and consistent photovoltaic performance, but also complete shape recovery, even after undergoing repeated bending at an extremely low radius (1 mm) without significant mechanical damage. This provides a potential application to stretchable and wearable energy power supply devices.